Oxidative stress mediated the inhibition of cerebral creatine kinase activity in silver catfish fed with aflatoxin B 1 -contaminated diet - Souza C.F. (2019)
© 2018, Springer Nature B.V. Aflatoxin B 1 (AFB 1 ) is an environmental toxicant and neurotoxic compound that induces the production of free radicals, causing oxidative stress. Creatine kinase (CK) is a central controller of energy metabolism in tissues with a large and fluctuating energy demand, and it is highly susceptible to inactivation by free radicals and oxidative damage. Thus, the aim of this study was to evaluate whether a diet for freshwater silver catfish (Rhamdia quelen) containing AFB 1 inhibits cerebral CK activity, as well as the involvement of the oxidative stress on this inhibition. Brain CK activity was lower on days 14 and 21 post-feeding in animals that received AFB 1 -contaminated diet compared to the control group (basal diet), similarly to the brain sodium-potassium pump (Na + , K + -ATPase) activity. On the other hand, lipid peroxidation and protein carbonylation levels were higher on days 14 and 21 post-feeding in animals fed with AFB 1 -contaminated feed compared to the control group, while the antioxidant capacity against peroxyl radicals and thiol content was lower. Based on these evidences, the data demonstrated that diet containing AFB 1 severely affects CK activity, an essential enzyme that plays an important role in brain energy homeostasis. Also, the impairment of energetic homeostasis linked with the use and generation of ATP via inhibition of CK activity elicited an inhibition of enzymes ATP-dependent, such as Na + , K + -ATPase. Moreover, the inhibition of brain CK activity appears to be mediated by the oxidation of lipids, proteins, and thiol group, as well as by a reduction in the antioxidant capacity.